Caries Risk Assessment and Dental Referral by Paediatric Primary Care Physicians in Sichuan Province, China: A Cross-Sectional Study - Wang Q; Qu X; Houser SH; Zhang Y; Tian M; Zhang Q; Zhang W (Dove Medical Press, 2022)
Qingyu Wang,1,2 Xing Qu,3 Shannon H Houser,4 Yan Zhang,5 Meirong Tian,3 Qiong Zhang,6,7 Wei Zhang3 1West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, People's Republic of China; 2HEOA Group, Institute for Healthy Cities and West China Research Center for Rural Health Development, Sichuan University, Chengdu, People's Republic of China; 3Institute of Hospital Management, West China Hospital, Sichuan University, Chengdu, People's Republic of China; 4Department of Health Services Administration, the University of Alabama at Birmingham, Birmingham, AL, USA; 5Department of Maternity and Child Health Management, Sichuan Provincial Maternity and Child Health Care Hospital, Chengdu, People's Republic of China; 6Department of Pediatric Dentistry, West China Hospital of Stomatology, Sichuan University, Chengdu, People's Republic of China; 7State Key Laboratory of Oral Diseases & National Clinical Research, Sichuan University, Chengdu, People's Republic of ChinaCorrespondence: Xing Qu, Institute of Hospital Management, West China Hospital, Sichuan University, No. 37 Guoxue Lane, Chengdu, 610041, People's Republic of China, +86 13880713452, Email qvxing@163.comBackground: Limited information is known about dental implementation by pediatric primary care physicians (PCPs) at the primary care level in China. This study aimed to explore the current status of primary oral care implementation and related influencing factors.Methods: A cross-sectional survey was conducted among PCPs in Sichuan Province, China. Multivariable logistic regression was used to analyse factors associated with CRA and dental referral for high caries-risk children.Results: A total of 504 out of 524 questionnaires remained for analysis. In all, 93.8% of PCPs reported that they usually or sometimes performed dental screening for children, 31.3% performed CRA, and 49.0% referred high caries-risk children to dentists. More CRA activities were associated with PCPs who encountered a greater number of children with caries during systematic care (adjusted OR: 2.37, 95% CI:[1.08,5.18], had dental knowledge training by pediatric dentists (aOR: 2.26, 95% CI:[1.36, 3.75], and learned pediatric dental knowledge on their own (aOR: 2.87, 95% CI: [1.51, 5.45]). In addition to the above associators, a higher rate of dental referrals for high caries-risk children was associated with having a dental department in the same work institute (aOR: 1.72, 95% CI: [1.09, 2.70] and having more confidence in their dental knowledge (aOR: 1.29, 95% CI: [1.04, 1.61]).Conclusion: Paediatric PCPs commonly implement dental screening but perform fewer CRAs and dental referrals for high caries-risk children during systematic health management in western China. To increase CRA activities and dental referral by paediatric PCPs, health policymakers could encourage interdisciplinary cooperation between dental professionals and paediatric PCPs.Keywords: caries risk assessment, dental referral, paediatric physicians, primary care, China